Climate change projections and hydrological modelling to predict the streamflow in Berach-Banas catchment, Rajasthan - Kuldeep Pareta; Yogita Dashora (Discover Water, 2025)
Abstract This study investigates the impact of climate change on streamflow dynamics in the Berach-Banas catchment of Rajasthan through climate projections and hydrological modeling. This study employs the MIKE Hydro River and NAM (Nedbor-Afstromings Model) Rainfall-Runoff modules, integrating data from 14-meteorological stations and two streamflow stations (Chittorgarh and Bigod) for period 2000–2022. Climate projections are derived from the CMIP6 (Coupled Model Intercomparison Project Phase 6) under the SSP2-4.5 (Shared Socioeconomic Pathways) scenario for the period 1951–2100. Sixteen downscaled Global Climate Models (GCMs) from various institutes are utilized to simulate future conditions for 2030, 2050, and 2090. The hydrological model incorporates ten water storage structures and delineates the catchments into 13 sub-catchments. The calibration period (2011–2015) demonstrated strong model performance at Chittorgarh (R2 = 0.92 with a water balance error (WBL) of 1.41%) and Bigod (R2 = 0.95, WBL of 0.99%). Similarly, the validation period (2017–2022) exhibited good performance at Chittorgarh (R2 = 0.91, WBL = 1.64%) and Bigod (R2 = 0.94, WBL = 1.13%). Sensitivity analysis identified CQOF (overland flow runoff coefficient), CK1,2 (time constants for routing overland flow), and Lmax (maximum water content in root zone storage) as critical parameters, consistent with findings from previous studies on Indian river basins. The climate change impact analysis indicated a consistent increase in streamflow rates for 2030, 2050, and 2090 compared to 2022, likely driven by rising temperatures and changes in precipitation patterns. The projected increase in streamflow rates underscore potential future challenges for water management, highlighting the need for effective adaptation strategies. The novelty of the study lies in its comprehensive integration of future climate scenarios with hydrological modeling, offering valuable insights for sustainable water resource planning in the region. The results highlight the substantial hydrological changes anticipated in the coming decades, enhancing the overall understanding of climate change impacts on water systems.